ХАЛҚ ДОСТОНЛАРИДА ЁШЛАР ТАРБИЯСИНИНГ ҚЎЙИЛИШИ - Нурбоев, Ш. (SCIENCE and SOCIETY, 2021)
This article provides feedback on the research results and literature on the problem of spiritual and moral issues related to the education of young people.